2007
DOI: 10.1521/suli.2007.37.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Injurious Behavior and Eating Disorders: The Extent and Nature of the Association

Abstract: We have reviewed the literature on the association between self-injurious behaviors (SIB) and eating disorders from the psychological-behavioral perspective. Our aims were to investigate the extent and possible reasons for the association. A literature search was conducted using the following electronic databases (1989-2005): Medline, PsychInfo and EMBASE. References in identified articles were also screened. The reported occurrence of SIB in eating disorder patients ranged between 25.4% and 55.2%. The figures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
180
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(224 citation statements)
references
References 58 publications
35
180
2
7
Order By: Relevance
“…To date, epidemiological data on the occurrence of NSSI in the context of ED have been scarce; NSSI estimates across ED studies have varied widely; and all reviews on the topic have been narrative (Sansone & Levitt, 2002;Svirko & Hawton, 2007;Kostro et al 2014). These limitations translate into a complete lack of aggregate and weighted quantitative data on NSSI in ED, which highlights the absence of a confident estimate of the true prevalence of NSSI among individuals with ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, epidemiological data on the occurrence of NSSI in the context of ED have been scarce; NSSI estimates across ED studies have varied widely; and all reviews on the topic have been narrative (Sansone & Levitt, 2002;Svirko & Hawton, 2007;Kostro et al 2014). These limitations translate into a complete lack of aggregate and weighted quantitative data on NSSI in ED, which highlights the absence of a confident estimate of the true prevalence of NSSI among individuals with ED.…”
Section: Introductionmentioning
confidence: 99%
“…Although we examined a variety of potential predictors of NSSI, we were particularly interested in the roles of: (a) diagnosis (anorexia v. bulimia) and diagnostic subtype within anorexia (eating-purging v. restrictive), in line with evidence that NSSI is more prevalent in individuals with binge and purge behaviours, i.e. patients with BN or those with the binge eating-purging subtype of AN (Svirko & Hawton, 2007); (b) history of attempted suicide, in line with evidence that NSSI shows a positive association with suicide risk in various unselected and clinical populations (Jacobson & Gould, 2007;Turner et al 2013;Kostro et al 2014); and (c) history of substance abuse, in line with evidence that individuals with substance disorders are more likely to self-injure (Klonsky & Muehlenkamp, 2007). Quantifying, for the first time, the association of NSSI with each of the above predictors makes a valuable contribution to the evidence base, which is again limited by the lack of weighted aggregate data.…”
Section: Introductionmentioning
confidence: 99%
“…4 ED inpatients, n=185, mean age=21a, some form of SIB in their recent history Favaro et al (2007) 4.8-13.9 community sample, n=934 Claes & Vandereycken (2007a) 38.6 (BN) ED n=70, mean age 22a Svirko & Hawton (2007) 25. 4-55.2 …”
Section: (Bn) 358 (Ednos)mentioning
confidence: 99%
“…The relationships between eating disorders and suicidal behaviour and non-suicidal selfharm have been examined primarily in eating disorder samples. Some studies suggest that suicide attempts and non-suicidal self-harm are found in more than half of bulimic patients (Franko & Keel, 2006;Svirko & Hawton, 2007). These rates appear higher in bulimia nervosa compared to anorexia nervosa, although it seems that there are similar rates of this behaviour in the anorexia nervosa purging-type as in bulimia nervosa (Favaro & Santonastaso, 2000;Nagata, Kawarada et al, 2000).…”
Section: Bulimia Nervosa and Self-harmmentioning
confidence: 99%
“…Possible common factors are impulsivity, obsessive-compulsive traits, dissociation, trauma, conflict in the family environment and sensitivity to cultural factors, among others. Both self-harm and eating disorders may represent failures in emotion regulation, and both forms of body practices could act as an attempt to a more affective coping (Dohm, Striegel-Moore, et al, 2002;Franko & Keel, 2006;Levitt, Sansone, et al, 2004;Svirko & Hawton, 2007).…”
Section: Bulimia Nervosa and Self-harmmentioning
confidence: 99%